History of Amalgamation of Northern and Southern Protectorates of Nigeria - Iyanda Kamoru Ahmed; Aisha Ibrahim Ningin (Papanda Publishier, 2022)
This paper discusses the History Of Amalgamation Of Northern And Southern Protectorates. This research work will be divided into various parts. Firstly, we shall start with preliminary definition of terms. According to Chambers Everyday Dictionary, Legal means “pertaining to”, according to law, “lawful”. Regime means administration amalgamation means “the blending of different things a close union”.1 According to Price, “colonies are territories which has been acquired by the Crown either by settlement, by cession, by purchase or by conquest, and were thus Crown property in which British authority was unassailable in domestic and international law. Nwabueze contends: that the effect of annexation of territory is to divest the sovereign of the territory so annexed of his sovereignty and to transfer it to the British Crown who then becomes the new sovereign of the colony with unlimited powers of Government and a complete dominion over its territory, the inhabitants of which becomes the Crown subjects. A protectorate on the other band implies primarily jurisdiction over the external affairs of the protected territory.